2012
DOI: 10.1038/emboj.2012.220
|View full text |Cite
|
Sign up to set email alerts
|

DEAD-box protein DDX3 associates with eIF4F to promote translation of selected mRNAs

Abstract: Here, we have characterized a step in translation initiation of viral and cellular mRNAs that contain RNA secondary structures immediately at the vicinity of their m 7 GTP cap. This is mediated by the DEAD-box helicase DDX3 which can directly bind to the 5 0 of the target mRNA where it clamps the entry of eIF4F through an eIF4G and Poly A-binding protein cytoplasmic 1 (PABP) double interaction. This could induce limited local strand separation of the secondary structure to allow 43S pre-initiation complex atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
327
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(353 citation statements)
references
References 59 publications
18
327
0
Order By: Relevance
“…98 The DEAD-box helicase DDX3 is not essential for global translation, but is required for the translation of specific transcripts (e.g., Cyclin E1) that contain secondary structures within their 5' UTRs. 99,100 We found that mTOR promotes the recruitment of DDX3 to the 5' mRNA cap in a 4E-BP1/2-dependent manner, 72 suggesting a mechanism whereby mTOR activity is required for the translation of DDX3-bound transcripts. DDX6 (also known as RCK or p54) is a highly conserved DEAD-box helicase that contributes to global and transcript-specific mRNA storage, translational repression, and decay.…”
Section: Mtorc1 Regulates the Cap Recruitment Of A Network Of Translamentioning
confidence: 95%
“…98 The DEAD-box helicase DDX3 is not essential for global translation, but is required for the translation of specific transcripts (e.g., Cyclin E1) that contain secondary structures within their 5' UTRs. 99,100 We found that mTOR promotes the recruitment of DDX3 to the 5' mRNA cap in a 4E-BP1/2-dependent manner, 72 suggesting a mechanism whereby mTOR activity is required for the translation of DDX3-bound transcripts. DDX6 (also known as RCK or p54) is a highly conserved DEAD-box helicase that contributes to global and transcript-specific mRNA storage, translational repression, and decay.…”
Section: Mtorc1 Regulates the Cap Recruitment Of A Network Of Translamentioning
confidence: 95%
“…One of these is additional eIF4A for which one might imagine a mechanism (60). The others represent different RNA helicases including DDX3, DDX41, DHX9, and DHX29 (61)(62)(63)(64). These alternate possibilities are extensively reviewed in Parsyan et al (65).…”
Section: Other Complicationsmentioning
confidence: 99%
“…We confirmed that DDX3 is required for Rac1 expression at the translational level [12] . The 5' untranslated region (UTR) of Rac1mRNA has a high GC content and may fold into a stable secondary structure; this feature conforms to previously determined DDX3 targets [13][14][15] . Knockdown of DDX3 reduces the translation of a reporter containing the Rac1 5 UTR.…”
Section: Research Highlightmentioning
confidence: 53%